Excess risk and resource utilization in dialysis-dependent patients undergoing total hip arthroplasty: insights from a nationally representative database - Maman, David; Steinfeld, Yaniv; Berkovich, Yaron (Frontiers in Surgery, 2026)
BackgroundTotal hip arthroplasty (THA) reliably restores function and quality of life in patients with end-stage hip disease. Individuals with end-stage renal disease (ESRD) requiring dialysis are vulnerable to perioperative complications due to immune dysfunction, hemodynamic instability, and impaired wound healing. Evidence on risk-adjusted outcomes remains limited.MethodsA retrospective cohort study was conducted using the Nationwide Inpatient Sample (2016–2022). Dialysis dependence was identified using ICD-10-CM Z99.2. Primary outcomes included in-hospital mortality, length of stay (LOS), and hospital charges; secondary outcomes were major complications. Propensity score matching (10:1 nearest neighbour) balanced baseline demographics and comorbidities. Survey weights were used for national estimates. Post-matching outcomes were compared using risk ratios (RR) with 95% CIs.ResultsAmong 1,957,284 THA patients, 2,730 (0.1%) were dialysis dependent. In unmatched analysis, dialysis dependence was associated with substantially increased in-hospital mortality (1.3% vs. 0.03%; crude RR: 31.9, 95% CI: 22.7–44.9). After 10:1 propensity-score matching, dialysis-dependent patients had 62.5% longer LOS (3.9 vs. 2.4 days, p < 0.01), 95.8% higher hospital charges ($98,454 vs. $60,741, p < 0.01), and persistently elevated in-hospital mortality (matched RR: 10.1, 95% CI: 6.3–16.2). Major complications were significantly more frequent.ConclusionDialysis dependence is a strong independent predictor of higher perioperative morbidity, mortality, and cost following THA. Targeted multidisciplinary optimization and enhanced perioperative care pathways are warranted.